2012
DOI: 10.1063/1.4711020
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced off-diagonal thermoelectric effect via indirect optical heating of incline-oriented CaxCoO2 thin film

Abstract: Articles you may be interested inOptical and mechanical mode tuning in an optomechanical crystal with light-induced thermal effects

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The voltage signals are believed to arise from the off-diagonal term of the Seebeck tensor along the thin film surface, which is present in the anisotropic layered materials when an inclined crystal orientation is constructed [2,3]. This laser-induced thermoelectric voltage (LITV) effect has the specifics that a temperature gradient applied along the film normal direction gives rise to a transverse voltage signals along the film in-plane direction [4][5][6][7] and has been applied in the light-detection devices with advantages of fast time and broad spectral response, operating at room temperature but no bias required [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The voltage signals are believed to arise from the off-diagonal term of the Seebeck tensor along the thin film surface, which is present in the anisotropic layered materials when an inclined crystal orientation is constructed [2,3]. This laser-induced thermoelectric voltage (LITV) effect has the specifics that a temperature gradient applied along the film normal direction gives rise to a transverse voltage signals along the film in-plane direction [4][5][6][7] and has been applied in the light-detection devices with advantages of fast time and broad spectral response, operating at room temperature but no bias required [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…These tilted thin films are referred to ALT materials, and the LITV response can be optimized by tailoring the film thickness and the inclined crystal orientation [6,7,11]. LITV signals have been detected in several cuprates [4][5][6][7][8][9][10][11][12][13][14][15] which are correlated with the perovskites of Ruddlesden-Popper family [16], since the layered structures can cause different transport properties in various atomic layers and then large anisotropic thermopower DS, a key factor to LITV effect [2,5]. LITV signals are observed scaling to the resistance of thin films [17], and the doping dependence always shows the same behaviors as the change in DS upon the charge carrier density [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…This effect relies on the longitudinal temperature difference, perpendicular to the material surface. Under short-pulse laser illumination, it has relatively high responsivity, while for CW excitation, the responsivity is extremely low 35,36 .…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the photoresponse of Ca x CoO 2 thin ($100 nm thick) films with an off-diagonal TE effect were designed to be very fast ($10 ns), but the conversion is very inefficient. 24 In the present study, we have demonstrated fast response mechanism and speeds up to 6.4 KHz or 25 ls were achieved. According to our thermal model, the TE response is limited in speed only by thermal diffusion through the optical penetration length A.…”
mentioning
confidence: 71%